Pengaruh Karakteristik Sosial Demografi Terhadap Kepemimpinan Kader: Survey di Wilayah Desa di Indonesia - Rohmani, Ngatoiatu; Utari, Dewi (Prosiding University Research Colloquium, 2020)
Community health volunteers (CHVs) are the manifestation of community participation in an attempt of solving health issues in their area. One of skill asset that must be possessed by CHVs is leadership. CHVs selection criteria based on socio-demographic characteristics need to be upgraded to support their role in moving the community towards a healthy Indonesian optimally. The aim of this study was to assess the leadership role of CHVs in Purwomartani village and its contributed factors. This study used a cross sectional design conducted in Purwomartani, Kalasan, Sleman using 53 respondents selected through purposive sampling technique. Data were collected using a validated questionnaires and analyzed using SPSS version 20.0. The respondent comprised 100.0 % females with an average age of 45 years and living as a housewife. Most CHVs have education level up to senior high school and above (83.1%) and have experience as CHVs ± 10 years. Multiple regression analysis revealed that factor contributed with role of leadership was experience of being CHVs (